Penerapan IPTEK dan Project Based Learning Penyedian Air Bersih dan Peningkatan Kualitas Air Layak Konsumsi di Pondok Pesantren Al Qur’an Nur Ikhlas, Desa Pedalaman, Kecamatan Tayan Hilir, Kabupaten Sanggau - Sutrisno, Sutrisno; Maratina, Dina; Asy'ari, Farida; Azmal, Azmal; Rohermanto, Agus; Rahmadi, Joni; Faizal, Ahmad (Kapuas, 2024)
The Al Qur'an Nur Ikhlas Islamic Boarding School is precisely located on Jalan Gusti Djafar, Pedalaman Village, Tayan Hilir District, precisely in Gang Ikhlas, Sanggau Regency, West Kalimantan Province. Areas that have not yet been touched by clean water or water standards suitable for consumption. This is all due to the unequal distribution of infrastructure provision, due to limited government budgets and foundation costs, which is an inhibiting factor in the availability of clean water for Islamic boarding school residents. To overcome this problem, community service activities are carried out with the aim of increasing knowledge about clean water quality standards and water processing skills suitable for consumption by residents as well as improving the health and welfare of residents at the Al Qur'an Nur Ikhlas Islamic Boarding School. The method that will be carried out is seeking training and direct practice in making drilled wells and processing water suitable for consumption which will later be installed and operated. The results are that residents at the Islamic boarding school know the water standards in accordance with Minister of Health Regulation Number 416/MENKES/PER/IX/1990, understand how to make drilled wells, provide water and purify water suitable for consumption and the health and welfare of residents at the Miningkat Islamic boarding school.